Effect of first-line biologic initiation on glucocorticoid exposure in children hospitalized with new-onset systemic juvenile idiopathic arthritis: emulation of a pragmatic trial using observational data - Peterson, Rosemary G.; Xiao, Rui; Katcoff, Hannah; Fisher, Brian T.; Weiss, Pamela F. (Pediatric rheumatology online journal, 2021)
Glucocorticoid exposure is a significant driver of morbidity in children with systemic juvenile idiopathic arthritis (sJIA). We determined the effect of early initiation of biologic therapy (IL-1 or IL-6 inhibition) on glucocorticoid exposure in hospitalized patients with new-onset sJIA. We emulated a pragmatic sequence of trials ("pseudo-trials") of biologic initiation in children (≤ 18 years) hospitalized with new-onset sJIA utilizing retrospective data from an administrative database from 52 tertiary care children's hospitals from 2008 to 2019. Eligibility window, treatment assignment and start of follow-up between biologic and non-biologic study arms were aligned for each pseudo-trial. Patients in the source population could meet eligibility criteria at several timepoints. Mixed-effects logistic regression was used to determine the effect of biologic initiation on in-hospital glucocorticoid exposure. Four hundred sixty-eight children met eligibility criteria, of which 19% received biologic therapy without preceding or concomitant initiation of immunomodulatory medications. This proportion significantly increased over time during the study period (p <  0.01). 1451 trial subjects were included across 4 pseudo-trials with 71 assigned to the biologic arm and 1380 assigned to the non-biologic arm. After adjustment, there was a trend toward decreased odds of glucocorticoid initiation in the biologic arm compared to the non-biologic arm (OR 0.39, 95% CI [0.13, 1.15]). Biologic initiation in children hospitalized with new-onset sJIA significantly increased over time and may be associated with reduced glucocorticoid exposure. The increasing use of first-line biologic therapy may lead to clinically relevant reductions in treatment-related adverse effects of glucocorticoid-reliant therapeutic approaches.